(untitled) (Journal of Human Sciences, 2023)
Solid theoretical grounds for First Language (L1) use in Second Language (L2) classes have been established over the past three decades. Most of these arguments are based on the assumption that L1 use can enhance L2 teaching and acquisition. Recently, several studies have been conducted to support these theoretical arguments in different contexts, including the Arabic context, where Arabic is the mother tongue of teachers and learners. The present study aims for an in-depth review of the research on classroom code-switching (CS) in the Arabic context during the past three decades. It attempts to identify the most common research areas on classroom CS in the Arabic context. The systematic review approach was adopted for this study. The conclusion drawn for the present review revealed that research on classroom CS in the Arabic context needs to be more extensive and covers only some geographical contexts. The results also revealed that the research on classroom CS in the Arabic context focused on three common research areas. These areas are "Perceptions of Classroom Participants OF Classroom CS", "Functions of Teachers’ and Students’ CS", and "Reasons for Classroom CS". However, more research needs to be done to measure the effects of classroom CS on learning and teaching English as a foreign language.